Case Report: Invasive Pentastomes, Raillietiella orientalis (Sambon, 1922), in a Free-Ranging Banded Water Snake (Nerodia fasciata) in North Central Florida, USA - Walden, Heather D. S.; Iredale, Marley E.; Childress, April; Wellehan, James F. X.; Ossiboff, Robert J. (Frontiers in Veterinary Science, 2020)
Raillietiella orientalis is an obligate, crustacean parasite that resides in the respiratory tract of definitive snake hosts. Common throughout southeastern Asia and Australia, R. orientalis is believed to have been introduced into southern Florida, United States along with Burmese pythons (Python bivittatus) in the 1990s. While the invasive range of Burmese pythons is restricted to southern Florida, R. orientalis has advanced north in the state in native snake species. R. orientalis were recovered from the lungs, trachea, oral cavity, and esophagus, of an emaciated adult female free-ranging banded water snake (Nerodia fasciata) in north central (Alachua County), Florida, USA. Concurrent findings included the recovery of Ochetosoma sp. trematodes from the oral cavity, and multifocal dermal lesions consistent with snake fungal disease (Ophidiomyces ophiodiicola). This is the first report of R. orientalis in north central Florida, well outside the invasive range of the Burmese python, documenting the substantial northward expansion of the known geographical range of this invasive pentastome in Florida.